A space stealth and cosmic radiation shielding composite: Polydopamine-coating and multi-walled carbon nanotube grafting onto an ultra-high-molecular-weight polyethylene/hydrogen-rich benzoxazine composite. (10th November 2022) - Cha, Ji-Hun; Jang, Woo-Hyeok; Noh, Jung-Eon; Choi, Won-Ho; Kim, Chun-Gon
Abstract: The application of stealth design to satellites provides an advantage in reconnaissance activities by evading ground observation and increasing survivability by preventing attacks from anti-satellite weapons. A shield that absorbs microwave irradiation was developed for incorporation into an ultra-high-molecular-weight polyethylene (UHMWPE)/hydrogen-rich benzoxazine composite for cosmic radiation shielding and to prevent electronic malfunction. Through the application of a polydopamine coating to UHMWPE followed by the grafting of carbon nanotubes, microwave absorption was achieved and the mechanical properties were improved. Moreover, radiation dose analysis confirmed that the proposed material exhibited a higher radiation shielding performance than conventional radar absorbing structures. Graphical abstract: Image 1